Translation Shift of Google Translate in Translating Sports News on CNN - Prayitno, Daniswara; Muchtar, Muhizar; Mono, Umar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This article is entitled “Translation Shift of Google Translate in Translating Sports News on CNN” into Bahasa Indonesia by using Google Translate”. The problems of this research are to find out find out kinds of class shift are used by “Google Translate” in translating CNN Sports News and To find out how the kinds of class shift are used in the translation. The research method is descriptive qualitative. The data of this research are collected from the data source, 'I felt my body was still capable': Meet the moms hoping to shine at the Olympics by George Ramsay, CNN in April 7, 2021, Paul Pogba follows Cristiano Ronaldo's lead by removing display drink during a press conference by George Ramsay, CNN in June 17, 2021 and Cristiano Ronaldo makes history at Euro 2020 as Portugal beats Hungary by Ben Church, CNN in June 16, 2021. Translated into bahasa Indonesia by using Google Translate are identified based on Catford’s theory in which explain about the type of class shift.